Installation of polyethylene terephthalate (PET) columns to promote the soil-bearing capacity of soft kaolin clay - Ng, Jun Shen; Muzamir, Hasan (King Saud University, 2025)
The reuse of disposal waste like polyethylene terephthalate (PET) plastic in a modified stone column method in ground improvement offers a reliable, sustainable, and cost-effective approach. The method is aimed at rectifying the problem of soft clay soil in terms of its engineering properties, which often lead to severe issues including soil settlement, soil particle dispersion, high compressibility, soil bulging, and erodibility. Previous studies have suggested the utilization of PET plastic in treating kaolin through stone column installation, but there is no direct examination including a comprehensive statistical analysis. This research examines kaolin, PET plastic, and kaolin reinforced with PET columns by implementing the relevant geotechnical means. It focuses on particle size distribution, Atterberg limits tests, relative density test, specific gravity test, standard Proctor test, permeability test, unconfined compressive strength test, and unconsolidated undrained triaxial test. By assessing the shear strength parameters of the control and reinforced samples, the influence of the number of columns, column diameter, column height, area replacement ratio, height penetration ratio, column height to column diameter ratio, volume replacement ratio, and confining pressure were considered. The results obtained from the investigation of PET reinforcement in single and group categories confirmed the enhancement of kaolin shear strength parameters, with optimum improvement of 48.42% and 56.53% at a penetration height of 100 mm coherent to the observed parameters. Hence, the results not only testify to the effectiveness of single and group PET columns but also highlight the environmental benefit of PET material in promoting sustainable construction.